1991
DOI: 10.3402/polar.v9i1.6777
|View full text |Cite
|
Sign up to set email alerts
|

The Janusfjellet Subgroup (Bathonian to Hauterivian) on central Spitsbergen: a revised lithostratigraphy

Abstract: The Janusfjellet Subgroup is a marine shelf to prodeltaic succession dominated by shales with subordinate siltstones and sandstones. The subgroup comprises a lower Agardhfjellet (Upper Bathonian -Berriasian) and an upper Rurikfjellet (Berriasian -Hauterivian) formation. Based on field work in central Spitsbergen the following subdivisions of the formations are proposed (units listed in ascending order).The Agardhfjellet Formation (up to 290 m thick) contains four members: Oppdalena fining upwards succession fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Four of the wells have complete core coverage of the Agardhfjellet Formation (i.e., an average thickness of about 250 m). The successions in the wells were correlated with the classical sections of the Agardhfjellet Formation in the Janusfjellet area, c. 10 km to the northeast of the CO 2 wells (Dypvik et al, 1991a;Mørk et al, 1999;, as shown in Fig. 2.…”
Section: Methodsmentioning
confidence: 75%
See 3 more Smart Citations
“…Four of the wells have complete core coverage of the Agardhfjellet Formation (i.e., an average thickness of about 250 m). The successions in the wells were correlated with the classical sections of the Agardhfjellet Formation in the Janusfjellet area, c. 10 km to the northeast of the CO 2 wells (Dypvik et al, 1991a;Mørk et al, 1999;, as shown in Fig. 2.…”
Section: Methodsmentioning
confidence: 75%
“…Lower to Middle Jurassic, coarse-grained units have so far been the most prolific petroleum reservoirs in the southwestern Barents Sea (Henriksen et al, 2011). Middle Jurassic to lowermost Cretaceous, deeper shelf sediments are found in Svalbard at Hopen, Kong Karls Land, Wilhelmøya, Sørkapp and in the Isfjorden area, while in the Early Cretaceous the shallow shelf shallowed upward to deltaic and flood-plain deposits which were later flooded by Aptian shelf deposits (Dypvik et al, 1991a;Mørk et al, 1999;Krajewski, 2004;Midtkandal et al, 2016;Grundvåg et al, 2017). The Middle Jurassic to Lower Cretaceous Janusfjellet Subgroup comprises the Agardhfjellet and Rurikfjellet formations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1B). In the study area, this member is a ca 70-meter-thick succession of grey to black shales and siltstones irregularly interbedded with concretionary siderite and dolomite, deposited in an open-marine shelf environment with estimated water depths of 100-150 meters (Dypvik et al 1991;Mørk et al 1999;Hammer et al 2011Hammer et al , 2012Hryniewicz et al 2015). It has been interpreted as a transgressive unit with slightly dysoxic shelf conditions and periodic fluctuation in the oxygenation of the bottom water (Nagy et al 2009;Hammer et al 2011Hammer et al , 2012Hjálmarsdóttir et al 2012).…”
Section: Palaeogeographic and Stratigraphic Settingmentioning
confidence: 99%